Pengaruh Faktor Maternal Ibu terhadap Kejadian Stunting pada Balita Usia 24-59 Bulan di Wilayah kerja UPT Puskesmas Sopaah Kabupaten Pamekasan - Dewi Kusuma Wardani (Media Gizi Kesmas, 2022)
Background: The incidence of stunting  still being a major nutritional problem for toddlers around the world. Stunting occurs due to various factors that hinder the baby's growth process during first 1000 days of life or from the time the baby is in the womb until he is 24 months after birth, but the occurrence is only seen after the toddler is 24 months old. Stunting has a short-term impact in the form of disturbances in cognitive development and long-term effects that can be permanent.Objectives: The purpose of this study was to analyze the influence of maternal factors on the incidence of stunting in toddlers among 24-59 months in the Working Area of Sopaah Primary Health Care on 2021.Methods: This type of research was observational analytic with a case control research design. The research sample was 54 consisting of 27 case samples and 27 control samples. The data used are primary data obtained from interviews with respondents and secondary data sourced from the respondent's MCH Handbook. Analysis of research data using the SPSS program to perform statistical tests of chi-square and Odds Ratio.Results: The results of this study indicate that there is a significant effect between maternal height during pregnancy (p-value = 0.000 ; OR = 16.000) and Hypertension (p-value = 0.021; OR = 4.086) with the incidence of stunting in toddlers among 24-59 months in Indonesia. The Working Area of the Sopaah Primary Health Care. Meanwhile, maternal age during pregnancy (p-value = 1,000) and interval of pregnancy (p-value = 0.776) had no effect on the incidence of stunting in toddlers among 24-59 months.Conclusions: the prevalence of stunting in the Work Area of the Sopaah Primary Health Care on 2021 has increased compared to 2019 and the maternal factors that influence the incidence of stunting in toddlers are maternal height and hypertension, while maternal age and interval of preganancy do not have a significant influenceKeywords: stunting, maternal height, maternal age, interval of pregnancy, hypertension